Generative networks for precision enthusiasts - Butter, Anja; Heimel, Theo; Hummerich, Sander; Krebs, Tobias; Plehn, Tilman; Rousselot, Armand; Vent, Sophia (SciPost physics, 2023)
SciPost Journals Publication Detail SciPost Phys. 14, 078 (2023) Generative networks for precision enthusiasts
Gesehen am 15.08.2023